Controlling shareholders' stock pledges and strategic change: the moderating effects of corporate governance. Issue 4 (28th May 2021) - Zhong, Xi; Wan, He; Peng, Qiuping
Abstract : Purpose: The authors analyze the effects of controlling shareholders' stock pledging on firms' strategic change behavior, and investigate how the balance of power between shareholders and analyst coverage moderates those effects. Design/methodology/approach: Employing fixed effects models, the authors test hypotheses based on Chinese listed company data from 2011 to 2017. Findings: Controlling shareholders' stock pledges has a negative effect on strategic change. As the balance of power among shareholders and/or analyst coverage increases, it mitigates the effect of controlling shareholder stock pledges on strategic change. In particular, the balance of power between shareholders and analyst coverage weakened the relationship between controlling shareholder stock pledges and strategic change. Lastly, after distinguishing family from nonfamily firms, the authors discovered that these findings only held for family firms. Originality/value: This study makes important contributions to strategic change, stock pledge and family firm literature, and also provides guidance on firms' strategic change practices.